2007
DOI: 10.5194/angeo-25-689-2007
|View full text |Cite
|
Sign up to set email alerts
|

On the location and structure of the artificial 630-nm airglow patch over Sura facility

Abstract: Abstract.Results are presented of the artificial optical emission of the atomic oxygen red line (the radiation of level O( 1 D) with a wavelength of 630 nm) from the HF-pumped ionosphere, obtained in September 2004 at the SURA heating facility situated near Nizhny Novgorod, Russia. For vertical pumping the airglow patch was increasingly displaced to the north, up to 7-8 • , with increasing reflection altitude. For large brightness of the emission, the airglow patch started to develop at the northern edge of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…The optical emission intensity is usually maximum near the magnetic field-aligned direction even when there is more pump power in other directions. These observations are consistent with previous results from HAARP (Pedersen et al 2003 and Sura (Grach et al, 2007(Grach et al, , 2012. These observations suggest that the mechanism which accelerates suprathermal electrons, believed to include upper-hybrid resonance, is aspect sensitive and more efficient parallel to the magnetic field line compared to the direction where most pump power is being transmitted.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The optical emission intensity is usually maximum near the magnetic field-aligned direction even when there is more pump power in other directions. These observations are consistent with previous results from HAARP (Pedersen et al 2003 and Sura (Grach et al, 2007(Grach et al, , 2012. These observations suggest that the mechanism which accelerates suprathermal electrons, believed to include upper-hybrid resonance, is aspect sensitive and more efficient parallel to the magnetic field line compared to the direction where most pump power is being transmitted.…”
Section: Resultssupporting
confidence: 92%
“…Early experiments performed at the EISCAT HF transmitter facility (Kosch et al 2000(Kosch et al , 2002b and High Frequency Active Auroral Research Program (HAARP) Carlson 2001, Pedersen et al 2003) showed the unexpected result that the pump-induced optical emissions were most intense close to the magnetic zenith (approximately 12°S of zenith at EISCAT). When the pump beam was directed between vertical and the magnetic field direction, the brightest optical emissions appeared displaced towards the magnetic zenith at EISCAT Rietveld et al, 2003Rietveld et al, , 2004, HAARP (Pedersen and Carlson 2001, Pedersen et al 2003 and Sura facilities (Grach et al, 2007(Grach et al, , 2012. This included cases where the most intense optical emissions occurred outside of the −3-dB locus of the pump beam for pumping in the vertical direction.…”
Section: Introductionmentioning
confidence: 99%
“…A series of night-sky portraits in the O( 1 D) line, which was recorded in September 15, 2004 and is shown in Fig. 7, illustrates the northward temporal displacement of the luminescence spot related to an increase in the PW reflection height up to 300 km and precipitation of energetic electrons along the geomagnetic field B 0 from the acceleration region to the denser layers of the atmosphere up to altitudes of about 250 km, where the luminescence is generated, the eastward spot motion due to a drift in the crossed electric and magnetic fields, and the formation of field-aligned structures in the perturbed region [85]. The experiments also confirmed the "magnetic-zenith" effect, i.e., an increase in the luminescence intensity during the PW propagation in the magnetic-field direction, which was discovered for the first time on the HAARP and EISCAT polar facilities [86,87].…”
Section: Acceleration Of Electrons Optical Luminescence and Additiomentioning
confidence: 98%
“…Recording of luminescence permits one to study the large-scale structure of the perturbed ionospheric region, in particular the fieldaligned plasma structures, the position of the luminescence area with respect to the ionospheric region "illuminated" by powerful radio emission, regular drift motion and irregular movements of the increasedluminescence areas, etc. Such studies on the "Sura" facility were also performed in collaboration with foreign partners [83][84][85]. A series of night-sky portraits in the O( 1 D) line, which was recorded in September 15, 2004 and is shown in Fig.…”
Section: Acceleration Of Electrons Optical Luminescence and Additiomentioning
confidence: 99%
“…Many phenomena in the HF-pumped volume such as artificial airglow, descending artificial ionization layers, and pump-induced plasma irregularities, exhibit dependence on the angle of incidence, α, between the pump beam and the vertical (Grach et al, 2007(Grach et al, , 2012(Grach et al, , 2018Kosch et al, 2004Kosch et al, , 2014Mishin et al, 2016;Najmi et al, 2015;Pedersen & Carlson, 2001;Pedersen et al, 2009;Rietveld et al, 2003;Sergeev et al, 2013;Yampolski et al, 2019). Understanding these phenomena requires a systematic study of the SEE properties' α dependence, particularly near gyroharmonics.…”
Section: 1029/2019gl082890mentioning
confidence: 99%